Bank specialization and zombie lending - Olivier De Jonghe; Klaas Mulier; Ilia Samarin (National Bank of Belgium, 2021)
Bank specialization leads to expertise, including knowledge on zombie borrowers and the negative impact they exert on healthy borrowers. This induces specialized banks to reduce zombie lending. The reduction in zombie lending is larger when the scope and opportunity cost of negative spillovers to healthy borrowers is larger; namely, when the fraction of sectoral labor stuck in zombie firms is larger or when the sector is expected to grow faster. Additionally, specialized banks reduce zombie lending less in sectors with higher asset specificity, as zombie firms' default (and potential asset fire sales) could trigger reductions in healthy borrowers' collateral values.
Keywords: G21; G3; L2; 330; Credit misallocation; Zombie lending; Bank specialization; Soft information